The reliability evaluation of the water surface remote monitoring satellite equipment - A. D. Gubarev; I. L. Yaschuk; Ya. V. Khilinskaya (Космические аппараты и технологии, 2021)
The work is devoted to the reliability and effectiveness of the water surface remote monitoring space system. Analysis of existing monitoring methods has shown a high potential for using nanosatellites to solve the problem. As an object of study, 3U CubeSat was chosen with a payload placed on board in the form of a hyperspectral camera. To assess the reliability of the system, a mathematical model on the failure rates of subsystems is proposed. The structural and parametric reliability of the object was investigated in the Windchill Risk and Reliability software complex, taking into account the cyclogram of work and the specifics of the degradation process of individual components due to the influence of an aggressive space environment. To assess the effectiveness of the nanosatellite application, the dependence of the accuracy of determining water pollution on the operability of the photodetector was analyzed, since the photodetector is the central link in the transmission of optical information. The effective measurement of brightness spectral coefficients over the entire service life of nanosatellite is also obtained. Minimum required number of operable pixels was identified for monitoring the water surface with sufficient accuracy and reliability.